Entre o rito e o cotidiano: as mulheres da Igreja Congregação Cristã no Brasil da cidade de Carapicuíba - Leite, Sérgio Araújo (2008)
The work on women of the Church Congregation of the Christian world in Carapicuíba investigates the arrival of that church in this city, after its establishment in Brazilian territory in the first wave petencostal caller and the participation of women in the name of its interior and general society, as relates to changes in the last two decades. The observation of everyday life of these women began in a state public school, especially in areas such as APM, the county of school, the conversations with other mothers responsible for pupils of the school. The posture of the problems these women face was shown, because at that moment, they are inspirations of the pedagogy of Christian Congregation. The maintenance of a speech by the church, apparently accepted by all, is in many respects, dribble by women in the context of modernity. Studying the church is considering the great conflict between those who seek consistency and maintenance of your home with the company coming changes and social needs of the Brazilian woman. Despite the changes to this woman in society, it sees itself with in the church, no change, at least in the speech, because the tolerance to many strange behavior the doctrine became evident. While the older hold fast to old habits, there is a new transforming the church. The woman's Pentecostal Christian Congregation remains in silence inside the church, but a management change, but in a discreet way, slower, with no open confrontations with the patience acquired by the teaching of the Christian Congregation, which percurte and transform the church itself